A call to honour in service of emergent India - Singh, Jaswant 1938- (New Delhi Rupa & Co., 2006)
India's foreign relations during the period 1998-2004; first hand account by former foreign minister of India.
Keywords: Singh, Jaswant -- 1938-.; India -- Foreign relations -- 1984-.; India -- Politics and government -- 1977-.